Memahami Pekerjaan Roh Kudus dalam Pelayanan Gereja Berdasarkan 1 dan 2 Timotius - Gidion Gidion (HARVESTER: Jurnal Teologi dan Kepemimpinan Kristen, 2019)
The importance of the work of the Holy Spirit in the Church's history over time becomes a basic need for researching understanding of the role of the Holy Spirit in the church service. So the goal of this research is to analyze the letter of 1 and 2 Timothy regarding the doctrine of the Holy Spirit's role in church services. Specifically, the study using the exegesis principles to approach texts, while among historical analysis, context analysis, syntax analysis, analysis morphology, and lexical analysis of the text. So the results of this study explained that the role of the Spirit is the Holy provide an affirmation that Jesus is Lord, lead servants of God in the time of trouble, equipping servant of the Lord with the gift of ministry (2 Tim. 1: 6), stating prophecy (1 Tim. 4: 1), giving the power airport (1 Tim. 4:14), guiding people believe, teach, reveals the mind of God, inspired preaching of the word of God. Abstrak: Pentingnya memahami pekerjaan Roh Kudus dalam sejarah gereja dari waktu ke waktu menjadi kebutuhan dasar untuk meneliti pemahaman tentang peran Roh Kudus dalam pelayanan gereja. Jadi tujuan dari penelitian ini adalah untuk menganalisis surat 1 dan 2 Timotius mengenai doktrin peran Roh Kudus dalam pelayanan gereja. Secara khusus, penelitian ini menggunakan prinsip-prinsip penafsiran untuk mendekati teks, sedangkan di antara analisis historis, analisis konteks, analisis sintaksis, analisis morfologi, dan analisis leksikal teks. Jadi hasil dari penelitian ini menjelaskan bahwa peran Roh adalah yang Kudus memberikan penegasan bahwa Yesus adalah Tuhan, memimpin hamba-hamba Allah di masa kesusahan, memperlengkapi hamba Tuhan dengan karunia pelayanan (2 Tim. 1: 6), yang menyatakan nubuat (1 Tim. 4: 1), memberikan kekuatan bandara (1 Tim. 4:14), membimbing orang-orang percaya, mengajar, mengungkapkan pikiran Allah, mengilhami pemberitaan firman Allah.